Surgical strategies in the management of thyroid cancer: Approach, complications - Villagómez Albán, Nelson Francisco; Pasquel Cataña, Carolina Salome; Valencia Bajaña, Leslie Melissa; Gortaire Macas, Josselyn Gabriela (RECIMUNDO, 2025)
Thyroid cancer is a type of cancer that originates in the thyroid gland, a small butterfly-shaped gland located in the front of the neck. 1 The thyroid gland produces hormones that 2 control the body's metabolism. 3 An exhaustive literature review was conducted on surgical strategies in the management of thyroid cancer, covering approach, complications, and long-term outcomes. Databases such as PubMed, Scopus, and Web of Science were consulted, using key terms such as "thyroid cancer", "surgery", "thyroidectomy", "complications", and "long-term outcomes". 4 Original studies, systematic reviews, and meta-analyses published in recent years were selected, prioritizing those with the highest methodological quality and clinical relevance. The treatment and follow-up of thyroid cancer have advanced considerably in recent decades, offering patients safer and more effective treatment options, as well as personalized follow-up strategies to ensure early detection of recurrences and improve long-term outcomes.